A não incidência das contribuições previdenciárias, sobre as verbas de caráter indenizatório: conceitos e definições de remuneração - Feitosa Júnior, Antonio Mendes (2014)
This paper deals with the non-social security tax on indemnities. We seek to study what the IRS has done to encompass these indemnifications in the calculation of the levy on the payroll, saw definitions and concepts of wage and salary always arguing the unconstitutionality of no impact of these funds on the basis of such calculation social contribution, without forgetting to analyze all the precepts and language studies and tax species. Fundamental basis for the study